2015
DOI: 10.1007/s12020-015-0702-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of 68Ga-DOTATATE PET/CT in patients with multiple endocrine neoplasia type 1 (MEN1)

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is a hereditary syndrome predisposing to many endocrine and neuroendocrine tumors (NET). Conventional imaging (CI) cannot provide satisfactory results for all the different types of MEN1-related tumors. Objective of this prospective observational study was to evaluate the role of (68)Ga-DOTATATE PET/CT in MEN1 compared to CI. Diagnostic performance of (68)Ga-DOTATATE PET/CT for the detection of NET was evaluated as well as the prognostic role of SUVmax. Eighteen patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 23 publications
1
99
2
Order By: Relevance
“…This later scenario would be downgraded to weakly supportive (a tentative diagnosis) of the diagnosis of ZES in patients with MEN1 (Table 4.B.2). This occurs because these patients very frequently have other nongastrinoma NETs including NF-pNETs, carcinoids (gastric, lung, thymus), pituitary and adrenal NETs, which may all be positive on somatostatin receptor scintigraphy imaging (SRI) with either 68 Ga-DOTATATE PET/CT or 111 In-DTPA-octreotide with SPECT/CT imaging, and thus a positive SRI result provides minimal support for the diagnosis of ZES [33, 163165]. …”
Section: Discussion and Proposal Of New Criteria To Support Thementioning
confidence: 99%
“…This later scenario would be downgraded to weakly supportive (a tentative diagnosis) of the diagnosis of ZES in patients with MEN1 (Table 4.B.2). This occurs because these patients very frequently have other nongastrinoma NETs including NF-pNETs, carcinoids (gastric, lung, thymus), pituitary and adrenal NETs, which may all be positive on somatostatin receptor scintigraphy imaging (SRI) with either 68 Ga-DOTATATE PET/CT or 111 In-DTPA-octreotide with SPECT/CT imaging, and thus a positive SRI result provides minimal support for the diagnosis of ZES [33, 163165]. …”
Section: Discussion and Proposal Of New Criteria To Support Thementioning
confidence: 99%
“…Moreover, 68 Ga-PET/CT is another accurate technique for detecting NF-PNEN, and it seems to have value in the prognosis of MEN1-related PNEN. 68 Ga-PET/CT could then be a promising tool helping in the management of these neoplasms [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-DOTA PET-CT was evaluated in three prospective studies [33, 35, 45] and one study reported the diagnostic value in a retrospective case series [39]. Albers et al [33] compared the diagnostic value of combined conventional imaging (EUS/MRI) with 68 Ga-DOTATOC-PET-CT for the diagnosis of dpNETs in routine follow-up in 33 MEN1 patients.…”
Section: Resultsmentioning
confidence: 99%